Characteristics and outcomes of percutaneous coronary interventions in patients with spontaneous coronary artery dissection. A study from the administrative minimum data set of the Spanish National Health System - Alfonso, Fernando; Fernández-Pérez, Cristina; del Prado, Náyade; García-Guimaraes, Marcos; Bernal, José Luis; Bastante, Teresa; del Val, David; García-Márquez, María; Elola, Javier (Frontiers in Cardiovascular Medicine, 2022)
Background: Coronary revascularization in patients with spontaneous coronary artery dissection (SCAD) is challenging. Indications and results of percutaneous coronary interventions (PCI) in SCAD patients are not well established. Aims: To assess indications and results of PCI in SCAD Methods: The minimum basic data set of the Spanish National Health System (years 2016-2019) was used to identify 804 episodes of acute myocardial infarction (AMI) and SCAD, with a crude in-hospital mortality rate of 3%. Of these, 368 (46.8%) patients were revascularized with PCI during admission whereas 436 (54.2%) were managed conservatively. Results: Revascularization and in-hospital mortality rates both declined over the study period (p for trend both <0.05). SCAD patients treated with PCI were older, more frequently male, and had higher frequency of diabetes, ST-segment elevation AMI and cardiogenic shock, compared to patients managed conservatively. The crude in-hospital mortality rate was higher in patients treated with PCI (4.9% vs 1.4%; p=0.004). However, after adjusting by propensity score (223 pairs) the in-hospital mortality rate was similar in the 2 groups (Adj OR: 1.21; 95%CI: 0.30-1.57; p=0.76). Readmissions at 30-days were higher in patients managed conservatively (7.1 vs 1.6%, p<0.001) and this difference was maintained after propensity score adjustment (Adj average treatment effect: 2% vs 12.2%; OR: 0.15; 95%CI: 0.04-0.45; p<0.001). Conclusion: Revascularization is frequently used in unselected patients with AMI and SCAD but its use is declining. Patients with SCAD treated with PCI have a higher in-hospital mortality but this appears to be explained by their adverse baseline clinical characteristics.